Newspeak in the 21st century - Edwards, David, 1962- (Pluto, 2009)
Since 2001, Media Lens has encouraged thousands of readers to challenge the filtered and distorted version of the world provided by major newspapers and broadcasters. The media responses, collected in Newspeak, are an exposé of the arrogance and servility to power of our leading journalists and editors. Picking up where the highly acclaimed and successful Guardians of Power (2006) left off, Newspeak is packed with forensic media analysis, revealing the lethal bias in 'balanced' reporting. Even the 'best' UK media -- the Guardian, the Independent, Channel 4 News and the BBC -- turn out to be cheerleaders for government, business and war. Alongside an A-Z of BBC propaganda and chapters on Iraq and climate change, Newspeak focuses on the demonization of Iran and Venezuela, the Israel-Palestine conflict, the myth of impartial reporting and the dark art of smearing dissidents.